Resilience of Processed Fishery MSME during The Covid-19 Pandemic in Makassar City - Cangara, Arie Syahruni; Fakhriyyah, Sitti; Gosari, Benny Audy Jaya; Hasani, Muh. Chasyim; Wahid, Abd; Sudrajat, Iman; Amri, Andi; ., Amiluddin; Fachry, Mardiana E. (Hasanuddin University, 2022)
The Covid-19 outbreak has had a serious impact on various aspects of life and so far no drugs and antivirals have been found to completely cure the outbreak. Covid-19 has also become a serious threat in the economic field, one of which is in the field of processing fishery products. This study aims to determine the resilience of MEMEs in processed fisheries before the pandemic and during the COVID-19 pandemic in Makassar City. The sample in this study were eight MSMEs processed fisheries in the city of Makassar which were selected by purposive sampling. Primary data collection was carried out by interview using the help of a questionnaire. The data that has been collected was analyzed using a qualitative descriptive method. The results of the study show that the adaptations or strategies adopted by MEMEs in processing fisheries in meeting their daily needs are grouped into three categories, namely: The first is an active strategy, namely carrying out various activities by self-employment. The second passive strategy is trying to avoid risks caused by non-economic shocks (e.g. reducing social costs, health, education, and surrendering to circumstances). Furthermore, the network strategy is for example establishing relationships to obtain assistance both informally and formally from other parties.